Aravind FAQs in ophthalmology - Venkatesh Prajna, N. (India : Jaypee Brother Medical Publishers, INC, 2013)
This book is a compilation of the frequently asked questions and the answers expected in a postgraduate ophthalmology examination. The examination time is a tough period-to any student facing it, and a quick and concise revision is required for the student to pass it. While this book is not a replacement to the standard textbooks in ophthalmology, it will boost the self-confidence of the postgraduates to face their exams with confidence. This questions have been painstakingly gathered over a 10-year period from the collective experience of several senior teachers at Aravind Eye Hospital, Madurai, Tamil Nadu, India and the answers have been constantly refined. Apart from the exam-oriented questions, this book contains examples of case sheet writing and different management scenarios, which will help the students to logically analyze and answer in a coherent manner. Book jacket.
Chapter01_Introduction 1 Chapter02_Cornea Chapter03_Uvea Chapter04_Glaucoma Chapter05_Lens and Cataract Chapter06_Retina Chapter07_NeuroOphthalmology Chapter08_Orbit Chapter09_Pediatric Ophthalmology and Strabismus Chapter10_Miscellaneous Case Sheet Writing
Incluye contenido
Incluye índice
Keywords: OPHTHALMOLOGY; CORNEA; GLAUCOMA; RETINA